Okręg Wołyń Armii Krajowej .......... 257 - Dudek, Tomasz; Maszkiewski, Jakub (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
THE HOME ARMY VOLHYNIA DISTRICTThis section discusses the history of the ZWZ-AK (The Home Army Union of Armed Struggle) in its Volhynia district during World War Two. In this paper, the author attempted to showcase the operations of individual units of the Polish underground resistance organisation in the Volhynia area which targeted the Soviets, the Germans, and the Ukrainians. The author attempted to reconstruct the staffing of individual underground resistance structures. The author did not ignore an important, yet little known issue of the Polish civilian self-defence organised against Ukrainian nationalists targeting the Polish population with criminal acts in the Volhynia area. The author reminded that although the self-defence structures were largely organised by the Polish Home Army, some of the self-defence elements in certain areas had no choice but to cooperate with the Soviet guerillas. The author found that it was the Polish self-defence operatives who allowed large clusters of Polish population to survive. The section culminates in the course of Operation Tempers and the combat operations of the Home Army 27th Volhynian Infantry Division.